Leptin Gene and Leptin Receptor Gene Polymorphisms in Alcohol Use Disorder: Findings Related to Psychopathology - Browning, Brittney D.; Schwandt, Melanie L.; Farokhnia, Mehdi; Deschaine, Sara L.; Hodgkinson, Colin A.; Leggio, Lorenzo (Frontiers in Psychiatry, 2021)
Comorbidity between alcohol use disorder (AUD) and other addictive and psychiatric disorders is highly prevalent and disabling; however, the underlying biological correlates are not fully understood. Leptin is a peptide hormone known for its role in energy homeostasis and food intake. Furthermore, leptin plays a key role in the activity of the hypothalamic-pituitary-adrenal (HPA) axis and of several neurotransmitter systems that regulate emotionality and behavior. However, human studies that have investigated circulating leptin levels in relation to AUD and affective disorders, such as anxiety and depression, are conflicting. Genetic-based analyses of the leptin gene (LEP) and leptin receptor gene (LEPR) have the potential of providing more insight into the potential role of the leptin system in AUD and comorbid psychopathology. The aim of the current study was to investigate whether genotypic variations at LEP and LEPR are associated with measures of alcohol use, nicotine use, anxiety, and depression, all of which represent common comorbidities with AUD. Haplotype association analyses were performed, using data from participants enrolled in screening and natural history protocols at the National Institute on Alcohol Abuse and Alcoholism (NIAAA). Analyses were performed separately in European Americans and African Americans due to the variation in haplotype diversity for most genes between these groups. In the European American group, one LEP haplotype (EB2H4) was associated with lower odds of having a current AUD diagnosis, two LEPR haplotypes (EB7H3, EB8H3) were associated with lower cigarette pack years and two LEPR haplotypes (EB7H2, EB8H2) were associated with higher State-Trait Anxiety Inventory (STAI-T) scores. In the African American group, one LEP haplotype (AB2H8) was associated with higher cigarette pack years and one LEP haplotype (AB3H2) was associated with lower Fagerström Test for Nicotine Dependence (FTND) scores. Overall, this study found that variations in the leptin and leptin receptor genes are associated with measures of alcohol use, nicotine use, and anxiety. While this preliminary study adds support for a role of the leptin system in AUD and psychopathologies, additional studies are required to fully understand the underlying mechanisms and potential therapeutic implications of these findings.